PENGARUH PERILAKU MEROKOK TERHADAP RESIKO PENYALAHGUNAAN NAPZA DI UPMI - Nurul Dalimunte; Ratna Sari Dewi Harahap (Jurnal Riset Hesti Medan, 2019)
There are many reasons behind teenage smoking behavior where smoking behavior is a dysfunction of the individual itself and the environment. This can be seen from the study of the development of adolescents who started smoking associated with the crisis of psycho-social aspects experienced during development, when a teenager is looking for identity. The efforts to find that identity, not all can go according to the desired expectations. Some adolescents do smoking as a compensatory method because there are some parties that have a big influence in the socialization process. Smoking behavior usually begins in adolescence even though the process of becoming a smoker has started since childhood. Adolescence is also an important period of risk for the development of long-term smoking behavior. In addition, smoking behavior is the entrance to other negative behaviors such as drug abuse and drinking alcohol. In this study researchers sought the influence of smoking behavior on the risk of drug abuse. The data in this study were obtained by distributing evaluation questionnaires to students. The results of this study obtained information about the effect of smoking behavior on the risk of drug abuse. The benefit of this research is to provide information to students about the dangers of smoking and the risk of drug abuse. The aim of this research is to produce information about the dangers of smoking and the risk of drug abuse. The results of this study indicate that smoking behavior among students at the Indonesian Community Development University (UPMI) majority has moderate smoking behavior. both of these studies see the risk of drug abuse in students at the Indonesian Community Development University (UPMI), the majority is not at risk. third, this study found a significant effect between smoking behavior and the risk of drug abuse on students at UPMI.Keywords: smoking, behavior, drug, abuse.